Technique For Teaching Reading Of Narrative Text ToThe Eighth Grade Students At SMP N 2 JatirotoIn 2015/ 2016 Academic Year - Wijayanti, Murdaningrum Retna; , Drs. Djoko Srijono, M. Hum (2016)
This research paper is to describe technique for teaching reading of narrative text to the eighth grade students at SMP N 2 Jatiroto in 2015/ 2016 Academic Year. The writer focuses on teaching reading of narrative text at the second semester conducting by the teacher. The purpose of this research are to know the techniques for teaching reading of narrative text used by the teacher and to know the problems faced by the teacher in teaching reading of narrative text at the eighth grade students of SMP N 2 Jatiroto in 2015/ 2016 Academic Year. The data are taken from all elements of teaching reading committed by the teacher and the students and other sources such as field note, syllabus, textbook, and lesson plan. The methods of collecting data are observation, interview, and documentation. The result of the research shows that the techniques for teaching reading of narrative text to the eighth grade students at SMP N 2 Jatiroto are translation activity and question-answer exercises. The problems of teaching reading of narrative text are limited vocabulary of the students, limited media use, and limited of time.